Drug utilization in the era of big data - Zin, Che Suraya (2018)
Big data in healthcare refers to electronic health data sets that are so large and complex that it would be difficult to manage and analyze using traditional software and data management tools and methods. Big data in healthcare is also known as large health care databases which is one of the sources for drug utilization study. It is often used to address research questions on drug use and drug effect such as evaluation of the processes of prescribing, dispensing and consumption of medicines to improve the quality use of medicines in populations. Large healthcare databases, which contain data collected during routinely delivered healthcare to patients, can serve as a valuable resource for generating actionable evidence to assist in medical and healthcare policy decision-making. The sources of large healthcare data include electronic medical records, health insurance claims and patient registries. Data may be collected on drug sales, prescriptions, drug distribution chain, pharmaceutical and medical billing. The scope of the databases may be international, national or local. The databases may be diagnosis-linked or non-diagnosis-linked. Diagnosis-linked data enable drug use to be analyzed according to patient characteristics, therapeutic groups, diseases or conditions and, in the best of cases, clinical outcome. A useful analysis requires an understanding of the sources and organization of the data. Harnessing the power of information contained in large healthcare databases, while paying close attention to their inherent limitations, is critical to generate rigorous evidence-base for medical decision-making and ultimately enhancing patient care.